Development of Interactive Multimedia Based on A Contextual Approach to Mathematics Learning to Improve Results Student - Tedy Putra; Titin Rahmayanti Rambe (Institut Agama Islam Negeri Palopo, 2023)
This research aims to develop interactive multimedia based on a contextual approach. This research is research and development. This research uses a 4-D development model which consists of four stages, namely define, design, develop, disseminate. However, this research only reached the development stage. The research was carried out at SD IT Bintang Langkat. The subjects in the research were 20 class IV students. The object in the research isinteractive multimedia based on a contextual approach. The collection techniques used are observation, tests and questionnaires. Data analysis techniques are (a) feasibility analysis of interactive multimedia based on a contextual approach; (b) analysis of the effectiveness of interactive multimedia based on a contextual approach. Based on the results of expert validation carried out on interactive multimedia based on a contextual approach, the results of expert validation with a percentage of 92.80% are categorized as very feasible, the results of validation of language experts with a percentage of 80.00% are categorized as feasible, and the results of media expert validation with a percentage of 93.05% categorized as very feasible. The results in the pretest trial were 2 students who completed and 18 students who did not complete with a percentage of 45%, while in the posttest trial there were 19 students who completed and 1 student who did not complete with a percentage of 83%.Â Based on this description, it can be concluded that interactive multimedia based on a contextual approach is very feasible and effective for class IV students at SD IT Bintang Langkat.Â